Report of the committee of experts on the application of conventions and recommendations. (Articles 19, 22 and 35 of the constitution.) International Labour Conference. 46th session, Geneva, 1962. Report III (part IV.) (International Labour Office, 1961)
Information and reports on the application of conventions and recommendations.